Quantum Chemical Study on Molecular and Electronic Structures of Methyl and Methoxyl Substituted Cu(II) and Ni(II) Benzoic Acid Hydrazides Ions - I. O. Adeoye; O. A. Odunola; M. A. Oladipo; B. Semire (E-Journal of Chemistry)
The electronic structures of model methyl and methoxyl substituted benzoic acid hydrazides of Ni(II) and Cu(II) complexes have been studied both at semi empirical level (PM3). The ortho-methoxyl is relatively stable which may be due to the formation of hydrogen bonds between methoxyl oxygen and hydrogen on hydrazide (CH30---HNNH; 1.817Å for Cu(II) and 1.806∼1.839∼ for Ni(II)). The change in torsion in the complexes affect π-electrons delocalization (complexes containing π-electrons system) and consequently affect the band gap which is a measure of electronic properties that control the reactivity of the complexes. The curves for ortho and para methoxyl substituted Cu(II) complexes intercept at 50° and 135°-144°, this could suggest that both complex ions can co-exist and react in very similar ways in solution under certain conditions.